PEMANFAATAN BUBUK BUAH KLUWAK (PANGIUM EDULE REINW) SEBAGAI PEWARNA ALAMI PADA KOSMETIK LIQUID EYELINER - Syafitri, Ayu Vidiana; Nieke Andina Wijaya; Nia Kusstianti; M.A Hanny Ferry Fernanda (Jurnal Tata Rias, 2025)
Makeup is a beautifier for women to increase their confidence to appear in public or just do activities outside. Eyeliner is one of the cosmetics for makeup that is used on the eyelids to create a more defined and dramatic eye impression. This study aims to make an eyeliner preparation from kluwak fruit powder (Pangium edule Reinw) and to find out the best formula as a natural dye in liquid eyeliner. Kluwak itself has tannins that produce a brown-black color and contains antioxidants that can ward off reactive molecules. This study was conducted observationally, using an experimental method, namely by mixing kluwak fruit powder with distilled water, dimethyl sulfoxide, PVP K30, and phenoxyethanol which produced the 3 best formulas. Then, testing the physical properties of the preparation was carried out including organoleptic tests, pH tests, homogeneity tests, viscosity tests, and panelists' preferences for the liquid eyeliner preparation. From the 3 formulas, the physical results are in accordance with the characteristics of liquid eyeliner, namely black, has a fairly smooth texture, is easy to apply, adheres well to the skin, has a pH of 5, a viscosity level of 259-818 mPa s, but has a deficiency in aroma. The results of this study state that kluwak fruit powder can be used as a dye in liquid eyeliner. However, it needs to be improved regarding the less homogeneous texture and aroma because it has a distinctive kluwak aroma that is disturbing, it is better to add other aromas as a neutralizer. Keywords: Kluwak fruit powder, liquid eyeliner, natural dyes